High-entropy graphite composite negative electrode material, preparation method thereof, negative electrode and lithium ion battery

By formulating a variety of transitional metal elements on the surface of lithium -ion battery negative materials, the problem of decay of lithium -ion battery attenuation under low temperature fast charge conditions is solved, and the reversible capacity and cycle stability of the material are improved.

CN119361633AActive Publication Date: 2025-01-24CHONGQING INNOVATION CENTER OF BEIJING INSTITUTE OF TECHNOLOGY +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411454558.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-10-15
Filing Date
2024-10-17
Publication Date
2025-01-24
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The performance of the existing lithium-ion battery anode materials has severely degraded under low temperature fast charging conditions, resulting in a decrease in lithium ion transmission rate and lithium dendrites generation, affecting the battery structure and performance.

Method used

The high -entropy graphite composite negative material, through the formation of the cover layer of a variety of transition metal elements on the surface of the graphite, reduce the opposite sex of the lithium -ion transmission, increase the reversible capacity and first effect of the material.

Benefits of technology

The lithium storage performance and cycle stability of the lithium -ion battery negative electrode material under low temperature fast charge conditions have been improved, and the service life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361633A_ABST
    Figure CN119361633A_ABST
Patent Text Reader

Abstract

The invention relates to the field of batteries, and discloses a high-entropy graphite composite negative electrode material and a preparation method thereof, a negative electrode and a lithium ion battery, the preparation method comprises the following steps: mixing graphite and a surfactant in a first solvent to obtain a solution A, mixing a plurality of transition metal element sources in a second solvent to obtain a solution B, the solution A and the solution B are mixed, the first solvent and the second solvent are removed, then heat treatment is conducted in an anaerobic environment, the negative electrode material is obtained, and the multiple transition metal element sources are selected from five or more of a scandium source, a titanium source, a vanadium source, a chromium source, a manganese source, an iron source, a cobalt source, a nickel source, a copper source, a zinc source, a zirconium source, a niobium source, a molybdenum source, a tantalum source and a tungsten source. According to the prepared negative electrode material, the surface of graphite is coated with a coating layer formed by multiple transition metal elements, so that the conductivity can be remarkably improved, more lithium storage active sites are provided, the impedance of the material in the lithium intercalation process is reduced, the reversible capacity of the material can be increased, and meanwhile, the first-effect improvement of the material is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of batteries, and in particular to a high-entropy graphite composite negative electrode material and a preparation method thereof, a negative electrode and a lithium-ion battery. Background Art

[0002] Although the current commercial lithium-ion battery negative electrode material mainly uses graphite material, its layered structure and low lithiation potential and other shortcomings cannot meet the application of graphite negative electrode materials in the field of low-temperature fast charging. In a low-temperature environment, the lithium ion transfer rate in the graphite negative electrode decreases as the temperature decreases. At the same time, under fast charging conditions, due to the inconsistent lithium ion transfer rate between the graphite negative electrode surface and the interlayer, lithium dendrites are easily generated on the graphite surface, causing battery performance degradation and even destroying the battery structure. Summary of the invention

[0003] The purpose of the present invention is to overcome the serious performance degradation of negative electrode materials during low-temperature fast charging, and to provide a high-entropy graphite composite negative electrode material and a preparation method, a negative electrode and a lithium-ion battery. The high-entropy graphite composite negative electrode material provided by the present invention forms a coating layer on the surface of graphite through a variety of transition metal elements, which reduces the anisotropy of lithium ion transmission in graphite, increases the reversible capacity and first efficiency of the material, and has good application prospects in low-temperature fast charging.

[0004] In order to achieve the above-mentioned object, the first aspect of the present invention provides a method for preparing a high entropy graphite composite negative electrode material, wherein the preparation method comprises: mixing graphite and a surfactant in a first solvent to obtain a solution A, mixing a plurality of transition metal element sources in a second solvent to obtain a solution B, mixing the solution A and the solution B for a third time, removing the first solvent and the second solvent to obtain a graphite composite, and heat treating the graphite composite in an anaerobic environment to obtain a negative electrode material;

[0005] Among them, the multiple transition metal element sources are selected from five or more of scandium source, titanium source, vanadium source, chromium source, manganese source, iron source, cobalt source, nickel source, copper source, zinc source, zirconium source, niobium source, molybdenum source, tantalum source and tungsten source.

[0006] A second aspect of the present invention provides a high entropy graphite composite negative electrode material, wherein, based on the total amount of the negative electrode material, the amount of the graphite is 96-99.5wt%, and the amount of the transition metal element is 0.5-4wt%.

[0007] The third aspect of the present invention provides a negative electrode, which comprises the negative electrode material prepared by the preparation method described in the first aspect of the present invention or the negative electrode material described in the second aspect of the present invention.

[0008] The fourth aspect of the present invention provides a lithium ion battery, comprising the negative electrode described in the third aspect of the present invention.

[0009] When preparing the negative electrode material of graphite coated with multiple transition metal elements, the present invention first uses a surfactant to modify the surface of graphite so that it is evenly dispersed in a first solvent to prepare a solution A, and at the same time, multiple transition metal element sources are dissolved in a second solvent to prepare a solution B, and then the first and second solvents are removed after mixing solution A and solution B, and the obtained graphite composite is heat-treated under anaerobic conditions to obtain the negative electrode material of graphite coated with multiple transition metal elements. That is, the present invention uses a liquid phase method to disperse multiple transition metal element sources on the graphite surface, and after heat treatment, the multiple transition metal elements are combined and evenly distributed on the graphite surface to form a coating layer, thereby reducing the anisotropy of the graphite material and then improving the lithium storage performance of the graphite.

[0010] The preparation method provided by the present invention has simple and safe preparation process, low cost, good continuity and is suitable for mass production.

[0011] In the negative electrode material of multiple transition metal elements coated graphite provided by the present invention, the coating elements include five or more of scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, zirconium, niobium, molybdenum, tantalum, and tungsten, wherein the coating layer formed by the transition metal elements can significantly improve the conductivity, provide more lithium storage active sites, reduce the impedance of the material during the lithium insertion process, and help increase the reversible capacity of the graphite negative electrode material; further, the transition metal elements can also effectively expand the interlayer spacing of the material, which is conducive to the embedding and extraction of lithium ions, and is conducive to enhancing the diffusion and insertion kinetics of lithium ions, which is beneficial to the improvement of the first effect of the graphite negative electrode. The negative electrode material of the transition metal element coated graphite provided by the present invention is used as the negative electrode material of a lithium ion battery, which has good application prospects in low-temperature fast charging. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 is a schematic diagram of the structure of the negative electrode material obtained in Example 1;

[0013] Figure 2 is an EDS image of the negative electrode material prepared in Example 1;

[0014] Figure 3 This is the 0.1C cycle rate test diagram of Example 1

[0015] Figure 4 This is the 1C cycle rate test chart of Example 1. DETAILED DESCRIPTION

[0016] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0017] The terms "first", "second" and "third" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first", "second" and "third" may explicitly or implicitly include one or more of such features.

[0018] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0019] A first aspect of the present invention provides a method for preparing a high entropy graphite composite negative electrode material, wherein the preparation method comprises: mixing graphite and a surfactant in a first solvent to obtain a solution A, mixing a plurality of transition metal element sources in a second solvent to obtain a solution B, mixing the solution A and the solution B for a third time, removing the first solvent and the second solvent to obtain a graphite composite, and heat treating the graphite composite in an anaerobic environment to obtain a negative electrode material;

[0020] Among them, the multiple transition metal element sources are selected from five or more of scandium source, titanium source, vanadium source, chromium source, manganese source, iron source, cobalt source, nickel source, copper source, zinc source, zirconium source, niobium source, molybdenum source, tantalum source and tungsten source.

[0021] The present invention uses a surfactant to activate the surface of graphite to obtain a modified graphite solution A, mixes the modified graphite solution A with a solution B containing multiple transition metal element sources, and performs heat treatment in an anaerobic environment to obtain a high-entropy graphite composite negative electrode material in which graphite is coated with multiple transition metal elements. That is, the present invention uses a liquid phase method to evenly distribute the transition metal elements on the surface of graphite to form a uniform coating layer, thereby improving the stability of the material, thereby enhancing the lithium storage performance of the graphite, and improving the low-temperature fast charging performance of the material.

[0022] The graphite may be artificial graphite, natural graphite, etc., and there is no particular requirement for the type of graphite.

[0023] In some embodiments, preferably, the mass ratio of the graphite to the surfactant is 5-25:1.

[0024] In some embodiments, preferably, the mass ratio of the graphite to the surfactant is 10-20:1.

[0025] The mass ratio of graphite to surfactant is related to the dispersion uniformity of graphite, which in turn affects the uniformity of the coating layer. The uniformity of the coating layer affects the specific capacity of the material. The present invention can further improve the specific capacity of the negative electrode material by optimizing the mass ratio of graphite to surfactant. The mass ratio of graphite to surfactant can be any value between any two numbers of 5:1, 7:1, 10:1, 13:1, 15:1, 17:1, 20:1, 22:1, and 25:1.

[0026] In some embodiments, preferably, the total mass ratio of the graphite and the surfactant to the total mass of the plurality of transition metal element sources is 20-80:1.

[0027] In some embodiments, preferably, the total mass ratio of the graphite and the surfactant to the total mass of the plurality of transition metal element sources is 30-40:1.

[0028] The total mass ratio of graphite and surfactant to the total mass ratio of multiple transition metal element sources affects the thickness of the coating layer, and then affects the specific capacity of the material. The mass ratio of the two preferred by the present invention can further improve the above performance. The mass ratio of graphite and multiple transition metal element sources can be any value between any two numbers in 20:1, 30:1, 31:1, 32:1, 33:1, 34:1, 35:1, 36:1, 37:1, 38:1, 39:1, 40:1, 50:1, 60:1, 70:1, and 80:1.

[0029] In some embodiments, preferably, the heat treatment temperature is 700-800° C. and the time is 1-4 h.

[0030] In some embodiments, preferably, the heating rate of the heat treatment is 4-6°C / min.

[0031] During the heat treatment process, parameters such as temperature, time, and heating rate affect the performance of the negative electrode material, such as reversible specific capacity, coulombic efficiency, capacity retention rate, etc. The preferred heat treatment temperature, time, and heating rate of the present invention can further improve the above performance. The heat treatment temperature can be any value between any two numbers of 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, and 800°C, the heat treatment time can be any value between any two numbers of 1h, 2h, 3h, and 4h, and the heating rate can be any value between any two numbers of 4°C / min, 5°C / min, and 6°C / min.

[0032] In some embodiments, preferably, the first solvent and the second solvent are independently water and / or ethanol. Using water and / or ethanol as the solvent is convenient for subsequent removal on the one hand, and improves the safety of the operation on the other hand. When the solvent is water and ethanol, there is no special requirement for the ratio of the two.

[0033] In some embodiments, preferably, the concentration of solution A is 0.1-0.5 g / mL.

[0034] In some embodiments, preferably, the concentration of solution B is 0.01-0.05 g / mL.

[0035] Solution A includes graphite, a surfactant and a first solvent, and solution B includes a plurality of transition metal element sources and a second solvent. The concentrations of solution A and solution B affect the thickness and uniformity of the coating layer, and thus affect the specific capacity of the negative electrode material. The preferred concentrations of the two solutions of the present invention are conducive to further improving the above performance. The concentration of solution A can be any value between any two numbers of 0.1g / mL, 0.2g / mL, 0.3g / mL, 0.4g / mL, and 0.5g / mL, and the concentration of solution B can be any value between any two numbers of 0.01g / mL, 0.02g / mL, 0.03g / mL, 0.04g / mL, and 0.05g / mL.

[0036] In some embodiments, preferably, the surfactant includes polyvinyl pyrrolidone and / or hexadecyl trimethyl ammonium bromide. The above surfactants are widely available and inexpensive, and are conducive to low-temperature decomposition reactions.

[0037] In some embodiments, preferably, the scandium source includes one or more of scandium chloride, scandium carbonate, scandium sulfate, and scandium nitrate.

[0038] In some embodiments, preferably, the titanium source includes one or more of titanium chloride, titanium carbonate, titanium sulfate, and titanium nitrate.

[0039] In some embodiments, preferably, the vanadium source includes one or more of vanadium chloride, vanadium carbonate, vanadium sulfate, and vanadium nitrate.

[0040] In some embodiments, preferably, the chromium source includes one or more of chromium chloride, chromium carbonate, chromium sulfate, and chromium nitrate.

[0041] In some embodiments, preferably, the manganese source includes one or more of manganese chloride, manganese carbonate, manganese sulfate, and manganese nitrate.

[0042] In some embodiments, preferably, the iron source includes one or more of ferric chloride, ferric carbonate, ferric sulfate, and ferric nitrate.

[0043] In some embodiments, preferably, the cobalt source includes one or more of cobalt chloride, cobalt carbonate, cobalt sulfate, and cobalt nitrate.

[0044] In some embodiments, preferably, the nickel source includes one or more of nickel chloride, nickel carbonate, nickel sulfate, and nickel nitrate.

[0045] In some embodiments, preferably, the copper source includes one or more of copper chloride, copper carbonate, copper sulfate, and copper nitrate.

[0046] In some embodiments, preferably, the zinc source includes one or more of zinc chloride, zinc carbonate, zinc sulfate, and zinc nitrate.

[0047] In some embodiments, preferably, the zirconium source includes one or more of zirconium chloride, zirconium carbonate, zirconium sulfate, and zirconium nitrate.

[0048] In some embodiments, preferably, the niobium source includes one or more of niobium chloride, niobium carbonate, niobium sulfate, and niobium nitrate.

[0049] In some embodiments, preferably, the molybdenum source includes one or more of molybdenum chloride, molybdenum carbonate, molybdenum sulfate, and molybdenum nitrate.

[0050] In some embodiments, preferably, the tantalum source includes one or more of tantalum chloride, tantalum carbonate, tantalum sulfate, and tantalum nitrate.

[0051] In some embodiments, preferably, the tungsten source includes one or more of tungsten chloride, tungsten carbonate, tungsten sulfate, and tungsten nitrate.

[0052] The scandium source, titanium source, vanadium source, chromium source, manganese source, iron source, cobalt source, nickel source, copper source, zinc source, zirconium source, niobium source, molybdenum source, tantalum source and tungsten source mentioned above can all undergo low-temperature decomposition reaction, which is conducive to forming a surface coating layer.

[0053] In some embodiments, preferably, the particle size D of the graphite 50 The particle size of graphite is 100-200μm. Graphite particles with smaller particle size have larger specific surface area and good ion conductivity, which is beneficial to improve the low-temperature fast charging performance of negative electrode materials. The particle size of graphite can be any value between any two numbers of 100μm, 150μm, and 200μm.

[0054] In some embodiments, preferably, the method for removing the first solvent and the second solvent comprises: subjecting the third mixed solution to any one of spray drying, solvent evaporation, freeze drying, suction filtration, and centrifugation.

[0055] When the solvent is evaporated, the solvent is evaporated after mixing. The temperature of evaporating the solvent is generally 60-140°C. Evaporate until the solution is gelatinous, and then weigh it every 10-20 minutes. When the weight change between the two times does not exceed 0.005g, it means that the solvent is evaporated.

[0056] In some embodiments, preferably, the method for removing the first solvent and the second solvent comprises: spray drying the third mixed solution, and the outlet temperature of the spray drying is 60-120° C. The outlet temperature during spray drying can be any value between any two of 60° C., 80° C., 100° C., and 120° C.

[0057] In some embodiments, preferably, the freeze-drying temperature is -20°C to -10°C, and the time is 24-32 hours. When freeze-drying is used, the temperature is any value between any two of -20°C, -15°C, and -10°C, and the time can be any value between any two of 24h, 26h, 28h, 30h, and 32h.

[0058] In some embodiments, preferably, the first mixing, the second mixing and the third mixing each independently include stirring. The present invention uses a liquid phase method to disperse multiple transition metal element sources on the graphite surface. The graphite and transition metal elements have good dispersion uniformity, so simple stirring and mixing can be used, which is simple to operate.

[0059] In some embodiments, preferably, the anaerobic environment is a vacuum environment or an inert gas environment.

[0060] In some embodiments, preferably, the vacuum degree of the vacuum environment is 500-10 Pa. The vacuum degree only needs to be anaerobic, and the vacuum degree can be any value between any two of 10 Pa, 50 Pa, 100 Pa, 150 Pa, 200 Pa, 300 Pa, 400 Pa, and 500 Pa.

[0061] In some embodiments, preferably, the inert gas of the inert gas environment includes one or more of helium, neon, argon, and krypton.

[0062] A second aspect of the present invention provides a high entropy graphite composite negative electrode material, wherein the high entropy graphite composite negative electrode material includes graphite, and a plurality of transition metal element layers coated on the surface of the graphite, wherein the plurality of transition metal elements are selected from five or more of scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, zirconium, niobium, molybdenum, tantalum, and tungsten.

[0063] In some embodiments, preferably, based on the total amount of the entropy graphite composite negative electrode material, the amount of the graphite is 96-99.5 wt %, and the total amount of the plurality of transition metal elements is 0.5-4 wt %.

[0064] In some embodiments, preferably, based on the total amount of the negative electrode material, the amount of each type of transition metal element in the plurality of transition metal element sources is independently 0-0.8 wt %.

[0065] In some embodiments, preferably, based on the total amount of the negative electrode material, the amount of each type of transition metal element in the plurality of transition metal element sources is independently 0-0.4 wt %.

[0066] Based on the total amount of the entropy graphite composite negative electrode material, the amount of the graphite can be any value between any two of 96wt%, 96.5wt%, 97wt%, 97.5wt%, 98wt%, 98.1wt%, 98.2wt%, 98.3wt%, 98.4wt%, 98.5wt%, 98.6wt%, 98.7wt%, 98.8wt%, 98.9wt%, 99wt%, 99.2wt%, 99.4wt%, and 99.5wt%, and the total amount of the plurality of transition metal elements can be 0.5wt%, 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2wt%, 2.5wt%, and 3wt%. , 3.5wt%, 4wt%, the sum of which is 100wt%, and the amount of each type of multi-transition metal element in the multiple transition metal element sources is independently 0, 0.02wt%, 0.05wt%, 0.08wt%, 0.1wt%, 0.13wt%, 0.15wt%, 0.17wt%, 0.2wt%, 0.22wt%, 0.25wt%, 0.3wt%, 0.33wt%, 0.35wt%, 0.38wt%, 0.4wt%, 0.42wt%, 0.45wt%, 0.47wt%, 0.48wt%, 0.5wt%, 0.52wt%, 0.55wt%, 0.58wt%, 0.6wt%, 0.7wt%, 0.8wt%.

[0067] The third aspect of the present invention provides a negative electrode, which comprises the negative electrode material prepared by the preparation method described in the first aspect of the present invention or the negative electrode material described in the second aspect of the present invention.

[0068] The fourth aspect of the present invention provides a lithium ion battery, comprising the negative electrode described in the third aspect of the present invention.

[0069] When preparing a high entropy negative electrode material of graphite coated with multiple transition metal elements, the present invention first uses a surfactant to modify the surface of graphite so that it is evenly dispersed in a first solvent to prepare a solution A, and at the same time, multiple transition metal element sources are dissolved in a second solvent to prepare a solution B, and then solution A and solution B are mixed and the above-mentioned solvent is removed, and the mixture is heat-treated under anaerobic conditions to obtain a high entropy negative electrode material of graphite coated with at least five transition metal elements, that is, the present invention uses a liquid phase method to disperse multiple transition metal element sources on the graphite surface, and after heat treatment, multiple transition metal elements are combined and evenly coated on the graphite surface, reducing the anisotropy of the graphite material, and then improving the lithium storage performance of the graphite. In the present invention, the structure and performance of the graphite coated with the transition metal elements can be effectively improved by controlling the amount ratio of graphite to surfactant, the amount ratio of graphite to multiple transition metal elements, and the parameters such as temperature and time during the heat treatment process.

[0070] The preparation method provided by the present invention has simple and safe preparation process, low cost, good continuity and is suitable for mass production.

[0071] The high entropy negative electrode material of transition metal element coated graphite provided by the present invention, the coated elements include five or more of scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, zirconium, niobium, molybdenum, tantalum, and tungsten, wherein the high entropy transition metal element coating layer can significantly improve the conductivity of the material, provide more lithium storage active sites, reduce the impedance of the material during lithium insertion, and help increase the reversible capacity of the graphite negative electrode material; in addition, the high entropy metal can also effectively expand the interlayer spacing of the material, which is conducive to the embedding and extraction of lithium ions, and is conducive to enhancing the diffusion and insertion kinetics of lithium ions, which is beneficial to the improvement of the first effect of the prepared negative electrode material. The high entropy graphite composite negative electrode material provided by the present invention is used as a negative electrode material for lithium-ion batteries, and has good application prospects in low-temperature fast charging.

[0072] According to a particularly preferred embodiment of the present invention, the preparation method comprises: performing a first mixing of graphite and a surfactant in a first solvent to obtain a solution A, performing a second mixing of a plurality of transition metal element sources in a second solvent to obtain a solution B, performing a third mixing of the solution A and the solution B, removing the first solvent and the second solvent to obtain a graphite composite, and heat treating the graphite composite in an anaerobic environment to obtain a negative electrode material;

[0073] Wherein, the multiple transition metal element sources include manganese source, cobalt source, nickel source, copper source and zinc source;

[0074] The mass ratio of graphite to surfactant is 12-18:1;

[0075] The total mass ratio of the graphite and the surfactant to the total mass ratio of the multiple transition metal element sources is 33-28:1;

[0076] The temperature of the heat treatment is 720-750°C, the time is 2-3h, and the heating rate of the heat treatment is 5°C / min.

[0077] The present invention will be described in detail below by way of examples. In the examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are conventional products that can be purchased commercially.

[0078] In the following examples and comparative examples, the distribution of transition metal elements was detected using a field emission scanning electron microscope (Hitachi, Japan);

[0079] The graphite content in the high-entropy graphite composite negative electrode material was analyzed using a thermogravimetric analyzer TGA2 (Mettler, Switzerland). The carbon content in the sample can be determined by the change in mass; the content of transition metal elements was tested using an inductively coupled plasma emission spectrometer (Agilent 725ES & Agilent 5110).

[0080] Example 1

[0081] Step (1): 100 g of artificial graphite with a particle size of 150 μm and 6.67 g of polyvinyl pyrrolidone were weighed, and then added into 533 mL of water, and stirred on a magnetic stirrer at a speed of 500 rpm for 12 h to obtain a modified graphite solution A;

[0082] Step (2): 0.60 g of nickel nitrate, 0.60 g of cobalt nitrate, 0.59 g of manganese nitrate, 0.62 g of copper nitrate and 0.63 g of zinc nitrate were weighed respectively, added to 60.95 ml of water, and stirred on a magnetic stirrer at 500 rpm for 12 h to obtain a solution B;

[0083] Step (3): mixing solution A and solution B, and stirring on a magnetic stirrer at a speed of 500 rpm for 12 hours to obtain a mixed solution, and spray drying the mixed solution to obtain a graphite composite, wherein the outlet temperature of the spray dryer is 120° C.;

[0084] Step (4): the graphite composite is heated to 740° C. at a rate of 5° C. / min in a vacuum environment with a vacuum degree of 10 Pa, and kept warm for 3 h, to finally obtain a high entropy graphite composite negative electrode material, which is recorded as A1.

[0085] Example 2

[0086] Step (1): weighing 100 g of artificial graphite with a particle size of 150 μm and 10.00 g of polyvinyl pyrrolidone, adding them to 550 mL of water, and stirring them on a magnetic stirrer at a speed of 500 rpm for 12 h to obtain a modified graphite solution A;

[0087] Step (2): 0.73 g of nickel nitrate, 0.73 g of cobalt nitrate, 0.71 g of manganese nitrate, 0.75 g of copper nitrate and 0.75 g of zinc nitrate were weighed respectively, added to 73.33 ml of water, and stirred on a magnetic stirrer at 500 rpm for 12 h to obtain a solution B;

[0088] Step (3): mixing solution A and solution B, and stirring on a magnetic stirrer at a speed of 500 rpm for 12 hours to obtain a mixed solution, and spray drying the mixed solution to obtain a graphite composite, wherein the outlet temperature of the spray dryer is 120° C.;

[0089] Step (4): The graphite composite is heated to 740°C at a rate of 5°C / min in a vacuum environment with a vacuum degree of 10 Pa, and kept warm for 3 hours to finally obtain a high entropy graphite composite negative electrode material, which is recorded as A2.

[0090] Example 3

[0091] Step (1): 100 g of artificial graphite with a particle size of 150 μm and 5.00 g of polyvinyl pyrrolidone were weighed, and then added into 525 mL of water, and stirred on a magnetic stirrer at a speed of 500 rpm for 12 h to obtain a modified graphite solution A;

[0092] Step (2): 0.52 g of nickel nitrate, 0.52 g of cobalt nitrate, 0.51 g of manganese nitrate, 0.53 g of copper nitrate and 0.54 g of zinc nitrate were weighed respectively, added to 52.55 ml of water, and stirred on a magnetic stirrer at 500 rpm for 12 h to obtain a solution B;

[0093] Step (3): mixing solution A and solution B, and stirring on a magnetic stirrer at a speed of 500 rpm for 12 hours to obtain a mixed solution, and spray drying the mixed solution to obtain a graphite composite, wherein the outlet temperature of the spray dryer is 120° C.;

[0094] Step (4): The graphite composite is heated to 740°C at a rate of 5°C / min in a vacuum environment with a vacuum degree of 10 Pa, and kept warm for 3 hours to finally obtain a high entropy graphite composite negative electrode material, which is recorded as A3.

[0095] Example 4

[0096] Step (1): 100 g of artificial graphite with a particle size of 150 μm and 20.00 g of polyvinyl pyrrolidone were weighed, and then added into 600 mL of water, and stirred on a magnetic stirrer at a speed of 500 rpm for 12 h to obtain a modified graphite solution A;

[0097] Step (2): 1.19 g nickel nitrate, 1.19 g cobalt nitrate, 1.17 g manganese nitrate, 1.22 g copper nitrate and 1.23 g zinc nitrate were weighed respectively, added to 120 ml water, and stirred on a magnetic stirrer at 500 rpm for 12 h to obtain a solution B;

[0098] Step (3): mixing solution A and solution B, and stirring on a magnetic stirrer at a speed of 500 rpm for 12 hours to obtain a mixed solution, and spray drying the mixed solution to obtain a graphite composite, wherein the outlet temperature of the spray dryer is 60° C.;

[0099] Step (4): the graphite composite is heated to 700° C. at a rate of 4° C. / min in a vacuum environment with a vacuum degree of 10 Pa, and kept warm for 4 h, to finally obtain a high entropy graphite composite negative electrode material, which is recorded as A4.

[0100] Example 5

[0101] Step (1): 100 g of artificial graphite with a particle size of 100 μm and 4.00 g of polyvinyl pyrrolidone were weighed, and then added into 520 mL of water, and stirred on a magnetic stirrer at a speed of 500 rpm for 12 h to obtain a modified graphite solution A;

[0102] Step (2): 0.26 g of nickel nitrate, 0.26 g of cobalt nitrate, 0.25 g of manganese nitrate, 0.26 g of copper nitrate and 0.27 g of zinc nitrate were weighed respectively, added to 26 ml of water, and stirred on a magnetic stirrer at 500 rpm for 12 h to obtain a solution B;

[0103] Step (3): mixing solution A and solution B, and stirring on a magnetic stirrer at a speed of 500 rpm for 12 hours to obtain a mixed solution, and spray drying the mixed solution to obtain a graphite composite, wherein the outlet temperature of the spray dryer is 90° C.;

[0104] Step (4): the graphite composite is heated to 800° C. at a rate of 6° C. / min in a vacuum environment with a vacuum degree of 10 Pa, and kept warm for 1.5 h, and finally a high entropy graphite composite negative electrode material is obtained, which is recorded as A5.

[0105] Example 6

[0106] The method of Example 1 is followed, except that nickel nitrate, cobalt nitrate, manganese nitrate, copper nitrate and zinc nitrate are replaced by equal masses of nickel chloride, cobalt chloride, manganese chloride, copper chloride and zinc chloride, respectively.

[0107] Example 7

[0108] The method of Example 1 is followed, except that nickel nitrate, cobalt nitrate, manganese nitrate, copper nitrate and zinc nitrate are replaced by equal masses of nickel carbonate, cobalt carbonate, manganese carbonate, copper carbonate and zinc carbonate, respectively.

[0109] Example 8

[0110] The method of Example 1 was followed, except that in step (3), the solvent was removed by evaporation, i.e., stirring at 100° C. and 500 rpm until the solution was completely evaporated. The obtained negative electrode material was recorded as A8.

[0111] Example 9

[0112] The method of Example 1 was followed, except that in step (3), the solvent was removed by freeze drying, i.e., the mixed solution was cooled with liquid nitrogen and then freeze dried for 24 h in a freeze dryer with the cold well temperature set at -59°C. The obtained negative electrode material was denoted as A9.

[0113] Example 10

[0114] The process was carried out in the same manner as in Example 1, except that the heat treatment temperature was 600° C. and the obtained negative electrode material was denoted as A10.

[0115] Embodiment 11

[0116] The process was carried out in the same manner as in Example 1, except that the heat treatment temperature was 900° C. and the obtained negative electrode material was denoted as A11.

[0117] Example 12

[0118] The process was carried out in the same manner as in Example 1, except that the mass of polyvinyl pyrrolidone was 50 g.

[0119] Example 13

[0120] The process was carried out in the same manner as in Example 1, except that the mass of polyvinyl pyrrolidone was 3.33 g.

[0121] Embodiment 14

[0122] The process is carried out in the manner of Example 1, except that the masses of nickel nitrate, cobalt nitrate, manganese nitrate, copper nitrate and zinc nitrate are 2.12 g, 2.24 g, 2.12 g, 2.1 g and 2.09 g, respectively.

[0123] Embodiment 15

[0124] The process is carried out in the manner of Example 1, except that the masses of nickel nitrate, cobalt nitrate, manganese nitrate, copper nitrate and zinc nitrate are 0.21 g, 0.2 g, 0.19 g, 0.22 g and 0.25 g respectively.

[0125] Comparative Example 1

[0126] The process was carried out in the same manner as in Example 1, except that no surfactant was added. The obtained material was recorded as D1.

[0127] Comparative Example 2

[0128] The process was carried out in the same manner as in Example 1, except that no mixture of multiple transition metal sources was added. The obtained material was recorded as D2.

[0129] Comparative Example 3

[0130] The process was carried out in the manner of Example 1, except that artificial graphite, surfactant and a mixture of various transition metal sources were added to 593.95 mL of water, stirred, and then spray-dried and heat-treated (i.e., mixed once without separate mixing). The obtained material was recorded as D3.

[0131] Comparative Example 4

[0132] Weigh 100 g of artificial graphite with a particle size of 150 μm, and then weigh 0.60 g of nickel nitrate, 0.60 g of cobalt nitrate, 0.59 g of manganese nitrate, 0.62 g of copper nitrate and 0.63 g of zinc nitrate respectively, and ball mill them with a ball-to-material ratio of 20:1, a rotation speed of 400 rpm, and a time of 6 h. Then, the ball-milled material is heat treated in the manner of Example 1, and the obtained material is recorded as D4.

[0133] The appearance of the materials obtained in the above-mentioned embodiments 1-15 is not much different. Taking embodiment 1 as an example, its structural schematic diagram is as follows: Figure 1 As shown in the figure (the side is cut off to observe its internal structure), it can be seen from the figure that the surface of graphite is covered with a transition metal element layer, and its EDS scan is as follows Figure 2 As shown in the figure, it can be clearly observed that the graphite surface has five transition metal elements, namely Ni, Co, Cu, Mn and Zn, which shows that multiple transition metal elements are successfully coated on the graphite surface.

[0134] The materials obtained from Examples 1-15 and Comparative Examples 1-4 were tested for component content, and the results are shown in Table 1.

[0135] Table 1 Component content test results

[0136]

[0137]

[0138] The negative electrode materials obtained in Examples 1-15 and Comparative Examples 1-4 were assembled into lithium-ion batteries and electrochemical performance tests were performed. The specific method is as follows:

[0139] (1) The negative electrode materials to be tested (A1-A15 and D1-D4), the conductive agent conductive carbon black Super P, and the binder (a mixture of the binder sodium carboxymethyl cellulose CMC and the binder styrene-butadiene rubber SBR in a mass ratio of 1:1) were weighed and mixed into a slurry in a mass ratio of 8:1:0.5:0.5, and then the slurry was coated on a copper foil with a 100 μm coater, vacuum dried at 80°C, and rolled to prepare a negative electrode sheet for a lithium-ion battery;

[0140] (2) Using the prepared battery negative electrode plate, a metal lithium sheet as a counter electrode, Celgard2325 as a separator, and an electrolyte using 0.9 mol / L lithium bis(fluorosulfonyl)imide (LiFSI) and 0.1 mol / L lithium difluorooxalatoborate (LiDFOB) dissolved in a mixed solution of isoxazole (IZ) and fluoroethylene carbonate (FEC) (the volume ratio of the two is 1:1), a CR2025 button battery is completed in an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm).

[0141] The constant current charge and discharge test of the negative electrode material was carried out using Land CT2001A produced by Wuhan Landian Electronics Co., Ltd. The battery was tested at -20°C and a voltage range of 0.01-1.5V (1C=372mA / g).

[0142] Taking Example 1 as an example, its first reversible specific capacity and first coulombic efficiency at 0.1C are as follows: Figure 3 As shown in the figure (the first three cycles were performed at room temperature 25°C, 0.1C activation and then 0.1C test at -20°C), the first reversible specific capacity and first coulombic efficiency at 1C are as follows Figure 4 As shown (the first three cycles in the figure are at room temperature 25℃, after 0.1C activation, and then 1C test at -20℃). Figure 3 and 4 It can be seen that the lithium-ion battery with the negative electrode sheet made of the negative electrode material of Example 1 has good cycle stability and capacity retention rate at high rates, indicating that the coating layer formed by multiple transition metal elements can effectively improve the cycle stability of the graphite negative electrode at low temperature and high rate.

[0143] Specifically, the test results of Examples A1-A15 and Comparative Examples D1-D4 at 0.1C and 1C are shown in Tables 2 and 3, respectively. The first reversible specific capacity and first coulombic efficiency in Table 2 are the test results of the first cycle at room temperature, and the first reversible specific capacity at 1C in Table 3 refers to the test results of the first cycle at -20°C and 1C after activation.

[0144] Table 2 0.1C electrochemical performance test results

[0145]

[0146] Table 3 1C electrochemical performance test results

[0147]

[0148]

[0149] It can be seen from Table 2 and Table 3 that compared with Comparative Examples 1-4, the lithium-ion batteries containing the negative electrode sheets made of the negative electrode materials of Examples 1-15 have both higher first-cycle coulombic efficiency and capacity retention rate, indicating that transition metal element coating can effectively improve the cycle performance and reversible specific capacity of lithium-ion batteries.

[0150] It can be seen from Examples 1, 6 and 7 that when the transition metal element source is nitrate, the anisotropic performance of the obtained negative electrode material is better than that of other types of transition metal element salts.

[0151] Combining Examples 1, 8 and 9, it can be seen that the use of spray drying to remove the solvent can further improve the first reversible specific capacity, capacity retention rate and other properties of the negative electrode material compared to freeze drying and solvent evaporation. Among them, spray drying is better than freeze drying. Freeze drying is due to solvent evaporation. This is mainly because spray drying can coat and re-granulate the original graphite particles, which is beneficial to further improve the performance, while freeze drying will make the material fluffy, and solvent evaporation is to simply coat the transition metal elements on the graphite surface.

[0152] Combining Examples 1, 10 and 11, it can be seen that when the heat treatment temperature is too low or too high, the electrochemical performance of the electrode material is reduced, indicating that a heat treatment temperature of 700-800° C. can further improve the above performance.

[0153] In combination with Examples 1 and 12-15, it can be seen that when the mass ratio of graphite and surfactant or the ratio of the total amount of graphite and surfactant to the total amount of multiple transition metal elements is too low or too high, the electrochemical performance of the electrode material is poor, indicating that the preferred mass ratio of graphite and surfactant and / or the ratio of the total amount of graphite and surfactant to the total amount of multiple transition metal elements of the present invention can further improve the above performance.

[0154] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a high entropy graphite composite negative electrode material, characterized in that: The preparation method comprises: performing a first mixing of graphite and a surfactant in a first solvent to obtain a solution A, performing a second mixing of a plurality of transition metal element sources in a second solvent to obtain a solution B, performing a third mixing of the solution A and the solution B, removing the first solvent and the second solvent to obtain a graphite composite, and performing a heat treatment on the graphite composite in an anaerobic environment to obtain a negative electrode material; Among them, the multiple transition metal element sources are selected from five or more of scandium source, titanium source, vanadium source, chromium source, manganese source, iron source, cobalt source, nickel source, copper source, zinc source, zirconium source, niobium source, molybdenum source, tantalum source and tungsten source.

2. The preparation method according to claim 1, wherein The mass ratio of graphite to surfactant is 5-25:1, preferably 10-20:1; And / or, the total mass ratio of the graphite and surfactant to the total mass ratio of the plurality of transition metal element sources is 20-80:1, preferably 30-40:

1.

3. The preparation method according to claim 1 or 2, wherein The heat treatment temperature is 700-800°C and the time is 1-4h; And / or, the heating rate of the heat treatment is 4-6°C / min.

4. The preparation method according to any one of claims 1 to 3, wherein The first solvent and the second solvent are independently water and / or ethanol; And / or, the concentration of solution A is 0.1-0.5 g / mL; And / or, the concentration of solution B is 0.01-0.05 g / mL.

5. The preparation method according to any one of claims 1 to 4, wherein: The surfactant includes polyvinyl pyrrolidone and / or hexadecyl trimethyl ammonium bromide; And / or, the scandium source includes one or more of scandium chloride, scandium carbonate, scandium sulfate, and scandium nitrate; And / or, the titanium source includes one or more of titanium chloride, titanium carbonate, titanium sulfate, and titanium nitrate; And / or, the vanadium source includes one or more of vanadium chloride, vanadium carbonate, vanadium sulfate, and vanadium nitrate; And / or, the chromium source includes one or more of chromium chloride, chromium carbonate, chromium sulfate, and chromium nitrate; And / or, the manganese source includes one or more of manganese chloride, manganese carbonate, manganese sulfate, and manganese nitrate; And / or, the iron source includes one or more of ferric chloride, ferric carbonate, ferric sulfate, and ferric nitrate; And / or, the cobalt source includes one or more of cobalt chloride, cobalt carbonate, cobalt sulfate, and cobalt nitrate; And / or, the nickel source includes one or more of nickel chloride, nickel carbonate, nickel sulfate, and nickel nitrate; And / or, the copper source includes one or more of copper chloride, copper carbonate, copper sulfate, and copper nitrate; And / or, the zinc source includes one or more of zinc chloride, zinc carbonate, zinc sulfate, and zinc nitrate; And / or, the zirconium source includes one or more of zirconium chloride, zirconium carbonate, zirconium sulfate, and zirconium nitrate; And / or, the niobium source includes one or more of niobium chloride, niobium carbonate, niobium sulfate and niobium nitrate; And / or, the molybdenum source includes one or more of molybdenum chloride, molybdenum carbonate, molybdenum sulfate, and molybdenum nitrate; And / or, the tantalum source includes one of tantalum chloride, tantalum carbonate, tantalum sulfate, tantalum nitrate and the like. And / or, the tungsten source includes one or more of tungsten chloride, tungsten carbonate, tungsten sulfate, and tungsten nitrate; And / or, the particle size D of the graphite 50 100-200μm.

6. The preparation method according to any one of claims 1 to 5, wherein: The method for removing the first solvent and the second solvent comprises: subjecting the third mixed solution to any one of spray drying, solvent evaporation, freeze drying, suction filtration, and centrifugation; Preferably, the method for removing the first solvent and the second solvent comprises: spray drying the third mixed solution, and the outlet temperature of the spray drying is 60-120°C.

7. The preparation method according to any one of claims 1 to 6, wherein: The first mixing, the second mixing and the third mixing each independently include stirring; And / or, the anaerobic environment is a vacuum environment or an inert gas environment.

8. A high entropy graphite composite negative electrode material, characterized in that: The high entropy graphite composite negative electrode material comprises graphite, and a plurality of transition metal element layers coated on the surface of the graphite, wherein the plurality of transition metal elements are selected from five or more of scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, zirconium, niobium, molybdenum, tantalum, and tungsten; Preferably, based on the total amount of the high entropy graphite composite negative electrode material, the amount of the graphite is 96-99.5wt%, and the total amount of the plurality of transition metal elements is 0.5-4wt%; Preferably, based on the total amount of the negative electrode material, the amount of each type of transition metal element in the plurality of transition metal element sources is independently 0-0.8 wt %, preferably 0-0.4 wt %.

9. A negative electrode, characterized in that It comprises the negative electrode material prepared by the preparation method according to any one of claims 1 to 7 or the negative electrode material according to claim 8.

10. A lithium ion battery, characterized in that: Comprising the negative electrode as claimed in claim 9.

Citation Information

Patent Citations

  • Graphite negative electrode material of low-temperature lithium ion battery and preparation method thereof

    CN108987687A

  • Spinel type high-entropy oxide electrode material and preparation method thereof

    CN110364717A

  • Safe modified graphite and preparation method thereof

    CN111384396A

  • High-entropy ceramic modified positive electrode material and preparation method and application thereof

    CN115050940A

  • Graphite modified material, graphite-based negative electrode active material and preparation method and application thereof

    CN115172743A